Wall Imaging for Unilateral Intracranial Vertebral Artery Hypoplasia with Three-dimensional High-isotropic Resolution Magnetic Resonance Images - Xian-Jin Zhu; Wu Wang; Bin Du; Lei Liu; Xin-Xin He; Li-Bin Hu; Xue-Bin Zhang; Zun-Jing Liu; Wei-Jian Jiang (Chinese Medical Journal, 2015)
Background:. There are few studies for evaluating wall characteristics of intracranial vertebral artery hypoplasia (VAH). The aim of this study was to determine wall characteristics of VAH with three-dimensional volumetric isotropic turbo spin echo acquisition (3D VISTA) images and differentiate between acquired atherosclerotic stenosis and VAH. Methods:. Thirty patients with suspicious VAH by luminograms were retrospectively enrolled between January 2014 and February 2015. The patients were classified as “acquired atherosclerotic stenosis” or “VAH” based on 3D VISTA images. The wall characteristics of VAH were assessed to determine the presence of atherosclerotic lesions, and the patients were classified into two subgroups (VAH with atherosclerosis and VAH with normal wall). Wall characteristics of basilar arteries and vertebral arteries were also assessed. The clinical and wall characteristics were compared between the two groups. Results:. Five of 30 patients with suspicious VAH were finally diagnosed as acquired atherosclerotic stenosis by 3D VISTA images. 25 patients were finally diagnosed as VAH including 16 (64.00%) patients with atherosclerosis and 9 (36.00%) patients with normal wall. In the 16 patients with atherosclerosis, plaque was found in 9 patients, slight wall thickening in 6 patients, and thrombus and wall thickening in 1 patient. Compared with VAH patients with normal wall, VAH patients with atherosclerosis showed atherosclerotic basilar arteries and dominant vertebral arteries more frequently (P = 0.000). Conclusions:. Three-dimensional VISTA images enable differentiation between the acquired atherosclerotic stenosis and VAH. VAH was also prone to atherosclerotic processes.